The Shift-Share Method: An Instrument for Analyzing the Dynamics of Industry Structure of the Economy - Trubnik Т. Ye.; Mazurenko О. К. (Statistics of Ukraine, 2019)
The socio-economic events of the latest years and uncertainties in the vectors of development of the economic environment cause the need for robust statistical assessment. An important area of studies of the modern economy is determining the type of economic growth. The shift-share method is applied to determine the effect of the impact of national, industrial and regional factors on the dynamics of economic growth. The shares of effects (effects of the impact) caused by national economy trends, industry mix and region-specific factors are identified and analyzed. The position of economic activities in the industry mix of the Kyiv economy is analyzed and assessed by indicators of gross value added and number of employees with consideration to three components. The impact of each of them caused by the national factors, the established industry mix of the national economy and the internal competitiveness of a specific industry of the region are characterized. Factor decomposition of the change in the indicators caused by the national component, industry-specific and region-specific effects reveals that the overall growth in the gross value added by economic activity in Kyiv is to a large extent conditional on the effective industry policy and to the least extent on regional factors. However, the employment reduction in the Ukrainian capital was caused by the impact of national and industry factors, and was not compensated by the positive local effect. It is revealed that the stable flagship position is taken by financial and insurance activities, in spite of recent reforms in the bank sector with cleansing the bank system from ineffective and nontransparent entities. Kyiv remains to be the core center for concentration of financial services. The progressive growth in the construction market meets the needs of the megalopolis with its increasing population. The residents’ desire to expand the dwelling size and improve the living conditions helps improve business climate in the construction sector, increase its growth rates and share in the gross regional product (indirectly, through the gross value added). The section “Information and telecommunications” stands steadily on the top positions. Its rapid development, as a signal of the digital economy, enables for momentary exchanges of information and services on the domestic and external market, thus creating favorable prospects. The analysis of the composition of the problem group and the outsider group among the economic activities reveals the stable presence of manufacturing and social industries. Enterprises of the sections “Manufacturing”, “Supply of electricity, gas, steam and conditioned air”, “Supply of water, sanitation, treatment of wastes” have a stock of problems and system drawbacks; they suffer from lack of investment and innovation, they have no strong orientation on the challenges of modernity and market needs, which weakens the positions of the Ukrainian capitals’ economy as the industrial center. It is proposed to use the graphic method for illustrating the distribution of economic activities in Kyiv by quality characteristics of operation. The factors accelerating or hampering the development of economic activities in the region are determined. Recommendations on management decisions related with future operation of industries referred to as “leaders”, “regulars”, problematic industries and outsiders are given.